Solar Exhaust Fan with Temperature Sensor - Hamzah, Shahron Adli; Suhaimi, Suhazlan; Yani, Achmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Household nowadays need to face the global warming and also have to face increase in cost of living. In this era also, especially Malaysia is the one of developer country, so there so many developments. So this situation can lead to many crises to the household for example dust, high temperature, and the increasing in the electrical bill. This study was aimed to develop solar exhaust fan with temperature sensor that can help the household to overcome the issue. The project used the evolutionary prototyping model. Quantitative method approaches were used for this study where 33 participants were participating in the survey before design the system and 32 respondent respond to survey during the user acceptance testing.